2015
DOI: 10.1021/acs.jchemed.5b00342
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Whiskey by Dispersive Liquid–Liquid Microextraction Coupled with Gas Chromatography/Mass Spectrometry: An Upper Division Analytical Chemistry Experiment Guided by Green Chemistry

Abstract: Analysis of whiskey samples prepared by a green microextraction technique, dispersive liquid–liquid microextraction (DLLME), before analysis by a qualitative gas chromatography–mass spectrometry (GC/MS) method, is described as a laboratory experiment for an upper division instrumental methods of analysis laboratory course. Here, aroma compounds in whiskey samples (n = 11) were extracted using ultrasound-assisted DLLME with chloroform (as extraction solvent). The chloroform extract was analyzed by GC/MS with da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…To measure the absolute concentrations of the main compounds in whiskies, high‐performance liquid chromatography (HPLC) analysis was conducted. Although whiskies consist of a wide variety of compounds, 12 well‐known major compounds (Nose et al., ; Owens, Zimmerman, Gardner, & Lowe, ) (Figure S1) were quantified in this work. The total concentration c Total of the 12 compounds increases fairly proportionally as the maturation time t mat increases, as shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…To measure the absolute concentrations of the main compounds in whiskies, high‐performance liquid chromatography (HPLC) analysis was conducted. Although whiskies consist of a wide variety of compounds, 12 well‐known major compounds (Nose et al., ; Owens, Zimmerman, Gardner, & Lowe, ) (Figure S1) were quantified in this work. The total concentration c Total of the 12 compounds increases fairly proportionally as the maturation time t mat increases, as shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%
“…The method used allowed for a good differentiation of distillates. Whereas the authors of [45] found discrete compounds in various types of whiskey for didactic purposes, and then the chromatographic profiles obtained by the GC/MS method were used to identify the whiskey. The analytical procedure was based on dispersive microextraction with chloroform.…”
Section: Alcoholic Beveragesmentioning
confidence: 99%
“…GC/MS separates and identifies components of complex sensory compound mixtures (Gates and Bull, 2008). Sensory compound profiles are dependent on the type of whisky being tested (such as bourbon, Scotch, and Canadian) (Piggott, 2016) and show similarities among different whiskies for the major volatile congeners they contain (Owens et al, 2016). Russell and Stewart (2014) also found that of the spectrometric analysis methods available, chromatography offers advantages in speed, selectivity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory compounds of interest found in the whisky samples in this study. The sensory descriptors are taken from other works synthesized by Owens et al (2016).…”
mentioning
confidence: 99%